2015
DOI: 10.1093/nar/gkv182
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CIITA-binding profile identifies sequence preferences that dictate function versus recruitment

Abstract: The class II transactivator (CIITA) is essential for the expression of major histocompatibility complex class II (MHC-II) genes; however, the role of CIITA in gene regulation outside of MHC-II biology is not fully understood. To comprehensively map CIITA-bound loci, ChIP-seq was performed in the human B lymphoblastoma cell line Raji. CIITA bound 480 sites, and was significantly enriched at active promoters and enhancers. The complexity of CIITA transcriptional regulation of target genes was analyzed using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 83 publications
2
38
0
Order By: Relevance
“…In contrast to studies based on reporter or ChIP‐seq analysis, our results imply a highly restricted transcriptional footprint for CIITA for cDCs in vivo. Studies using cell lines found that CIITA could activate promoters of genes that are highly expressed in cDCs, such the Ii (CD74) , consistent with reports that CIITA binds to the Ii locus . By contrast, we find no regulation of Ii by CIITA in cDCs in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to studies based on reporter or ChIP‐seq analysis, our results imply a highly restricted transcriptional footprint for CIITA for cDCs in vivo. Studies using cell lines found that CIITA could activate promoters of genes that are highly expressed in cDCs, such the Ii (CD74) , consistent with reports that CIITA binds to the Ii locus . By contrast, we find no regulation of Ii by CIITA in cDCs in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…The SXY module was identified at the promoter of numerous genes in the MHC locus and was thus thought to restrict the activity of CIITA to this region of the genome . Subsequently, whole‐genome sequencing and ChIP‐seq in CIITA‐deficient B cell lines have revealed SXY modules and CIITA binding sites across the genome, expanding the putative genomic footprint of CIITA . Bioinformatic analyses and in‐vitro promoter assays have identified genes with proximal CIITA‐binding sites that are putatively regulated by CIITA and that are predicted to have functions related to antigen processing and presentation .…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of methyltransferases restored binding of both factors and led to high HLA-DQA1 and DQB1 expression. 27,28 These results suggest an importance of the promoter proximal regions of these genes and their methylation status. However, this observation was made in the cell lines derived from acute lymphocytic leukaemia, where different types of regulation can be involved.…”
Section: Discussionmentioning
confidence: 75%
“…showed that two important transcription factors that help to form enhanceosome, RFX and CIITA, did not bind to the hypermethylated promoter proximal regions of HLA‐DQA1 and DQB1 genes. Inhibition of methyltransferases restored binding of both factors and led to high HLA‐DQA1 and DQB1 expression . These results suggest an importance of the promoter proximal regions of these genes and their methylation status.…”
Section: Discussionmentioning
confidence: 76%
“…Whatever this additional domain confers different functions to the isoform I is still not clear. The isoform III is the best characterized among the three isoforms 2 , since it was the first discovered and has been used in diverse studies involving protein knockout or overexpression to investigate the CIITA regulation, activities and also its applicability in immunotherapies [25][26][27][28][29][30][31][32][33][34] .…”
Section: Source: Reith Et Al 2005mentioning
confidence: 99%